2021
DOI: 10.1002/smll.202100722
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Zinc Salt in Ultrathin Heterogeneous Film to Stabilize Zinc Metal Anode

Abstract: Aqueous zinc metal batteries (AZMBs) have drawn great attention due to the high theoretical capacity, low redox potential, and abundance reserves. However, the practical application of rechargeable AZMBs are hindered by the poor reversibility of Zn metal anode, owing to easy dendrite growth and serious side reactions. Herein, the preparation of heterogeneous interfacial film with highly dispersed and confined zinc salt in a 2D channel by coassembling polyamide 6, zinc trifluoromethanesulfonate, and layered dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…For instance, an ultrathin film composed of polyamide 6 (PA6), zinc trifluoromethane-sulfonate (Zn(TfO) 2 ) and layered double hydroxides (LDHs) (PA6/Zn(TfO) 2 /LDH) was reported to stabilize Zn metal anodes. 289 The interlayer space between PA6 and LDHs achieved the robust confinement of Zn(TfO) 2 via unique hydrogen bond networks in the PA6/Zn(TfO) 2 /LDH film (Fig. 11h), which could not only boost the fast and homogeneous Zn 2+ diffusion at the interface, but also significantly prevent the erosion of Zn metal anodes from H 2 O/O 2 to avoid the decomposition of electrolyte.…”
Section: A Summary Of Solvation Structure Regulation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, an ultrathin film composed of polyamide 6 (PA6), zinc trifluoromethane-sulfonate (Zn(TfO) 2 ) and layered double hydroxides (LDHs) (PA6/Zn(TfO) 2 /LDH) was reported to stabilize Zn metal anodes. 289 The interlayer space between PA6 and LDHs achieved the robust confinement of Zn(TfO) 2 via unique hydrogen bond networks in the PA6/Zn(TfO) 2 /LDH film (Fig. 11h), which could not only boost the fast and homogeneous Zn 2+ diffusion at the interface, but also significantly prevent the erosion of Zn metal anodes from H 2 O/O 2 to avoid the decomposition of electrolyte.…”
Section: A Summary Of Solvation Structure Regulation Strategiesmentioning
confidence: 99%
“…11h), which could not only boost the fast and homogeneous Zn 2+ diffusion at the interface, but also significantly prevent the erosion of Zn metal anodes from H 2 O/O 2 to avoid the decomposition of electrolyte. 289 Moreover, a cellulose nanowhisker-graphene (CNG) membrane, assembled with graphenes (GNs) and cellulose nanowhiskers (CNWs) could also function as a de-solvation layer to prevent H 2 O molecules from encountering the anode surface. 286 The researchers demonstrated that the CNWs showed strong interaction with H 2 O molecules and [Zn(H 2 O) 6 ] 2+ complexes due to the high adsorption energy, and the CNG membrane could attract [Zn(H 2 O) 6 ] 2+ and then take off H 2 O molecules via hydrogen bond interaction (Fig.…”
Section: A Summary Of Solvation Structure Regulation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the organic ion regulators, the polarization is generally very high, which hinders the rate performance of the battery. [28][29][30][31][32] The inorganic ion regulators were reported with small polarization, yet they either go through multiple preparation procedures, 33 or improved mechanical properties of the coating layer are requested. 34 Thus, it is signicant to explore the surface coating layer for Zn anodes to alleviate the disadvantages of electron or ion regulators, in the meantime, with a facile preparation method.…”
Section: Introductionmentioning
confidence: 99%
“…To induce a homogeneous plating/stripping, considerable efforts have been devoted, i.e., developing new/highly concentrated electrolytes, fabricating an artificial solid electrolyte interface (SEI), and introducing solid electrolyte. Another effective strategy is engineering a three-dimensional (3D) framework collector to decrease local current density that induces uniform Li nucleation and prevents dendrite growth . The 3D frameworks with porous structures provide buffer spaces to reduce volume changes. However, these 3D frameworks generally fail to display lithiophilicity, which results a high nuclear barrier and makes it impossible to use directly for metal anode collectors.…”
Section: Introductionmentioning
confidence: 99%